Efektifitas Pendekatan Game Based Learning untuk Meningkatkan Sikap Antisipasi Siswa terhadap Perilaku Pelecehan Seksual di Sekolah Pinggiran - Soraya, Syazarah; Hasanah, Uswatun; Hariati, Emy (Journal of Practice Learning and Educational Development, 2025)
This research is motivated by the high vulnerability of elementary school students in rural areas to sexual harassment due to a lack of understanding of self-limitations, social norms, and low environmental control. Appropriate sexual education at an early age is considered a preventive strategy, but it remains a sensitive issue. Therefore, this study aims to test the effectiveness of the Game Based Learning (GBL) approach in improving students' anticipatory attitudes towards sexual harassment. The research method used is quantitative with a true experimental design of the pretest-posttest control group design. The subjects were fifth-grade students at SD Negeri 050740 Kwala Langkat who were divided into two groups: group A with GBL and group B with Story Based Learning. Data were collected through questionnaires and observations, then analyzed using independent sample t-tests and gain scores. The results showed that GBL had a significant effect on improving students' anticipatory attitudes with a significance value of 0.001 <0.05. The effectiveness test also showed an average gain score of 0.52, which is in the moderate category. These findings demonstrate that GBL is an effective, interactive, and enjoyable learning approach for equipping students with the skills to recognize and respond to potential sexual harassment. This study recommends further development of GBL with a variety of media and collaborative integration between schools and parents to optimize its impact.